DIHYA, AN INTELLIGENT LEARNING OBJECTS REPOSITORY - ROUABAH, Abdelbasset; Supervisor: AKHROUF, Samir (University of M'sila, 2015)
E-Learning, which is based on the supply of educational content in a digital environment, has led to the creation of reusable, interoperable and shareable Learning Objects, accessible via the Learning Objects Repositories. Despite their many features, these LORs have some limitations. In order to eliminate them, these LORs need to become more intelligent and adaptive which is the role of Multi-Agents systems. This dissertation is divided into five chapters, we have gone through the state of art of LOS, and the Metadata standards associated with them, the LORs and the way to create Intelligent Learning Objects by merging the LOS and the agent paradigm; then we presented the conceptual study, with a detailed analysis of the repository and its different functions. My principal aim was to clear the air on these technologies, by providing an unbiased and independent outlook and to develop an Intelligent LOR dedicated to computer science educational institutions that recommends its content to students according to their behavior patterns and academic standing.
Keywords: E-Learning, Learning Objects, Learning Objects Repositories, Multi-agent systems, Intelligent Learning Objects, Recommender Systems, Artificial Intelligence.